The Influence of Company Size, Fixed Asset Intensity, Leverage, Profitability, and Political Connection To Tax Avoidance - Aminah Aminah; Chairina Chairina; Yohana Yustika Sari (AFEBI Accounting Review, 2017)
This study examines the influence of company size, fixed assets intensity, leverage, profitability and political connections against tax avoidance in manufacturing companies listed in the Indonesian Stock Exchange in the period of 2011-2015.This study forms an associative research. The population used in this study are manufacturing companies listed in the Indonesian Stock Exchange. The sample used as many as 53 manufacturing companies listed in the Indonesian Stock Exchange in the period of 2011-2015 that are selected with the purposive sampling method, and so the number of sample data is 265 data. Tax Avoidance in this study was measured using the cash effective tax rate (CETR). Data can be analyzed by using the logistic regression.The result showed that the profitability and political connections have influences to tax avoidance. While company size, intensity fixed assets and leverage do not influence tax avoidance.Keywords: Company Size, Intensity Fixed Assets, Leverage, Profitability, Political Connections, Tax Avoidance